2016
DOI: 10.1073/pnas.1608873113
|View full text |Cite
|
Sign up to set email alerts
|

Nonoverlapping roles of PD-1 and FoxP3 in maintaining immune tolerance in a novel autoimmune pancreatitis mouse model

Abstract: PD-1 (programmed-death 1), an immune-inhibitory receptor required for immune self-tolerance whose deficiency causes autoimmunity with variable severity and tissue specificity depending on other genetic factors, is expressed on activated T cells, including the transcription factor FoxP3 + Treg cells known to play critical roles in maintaining immune tolerance. However, whether PD-1 expression by the Treg cells is required for their immune regulatory function, especially in autoimmune settings, is still unclear.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
115
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(123 citation statements)
references
References 41 publications
8
115
0
Order By: Relevance
“…These findings suggest that Treg cells may be more susceptible to epigenetic modifications by bromodomain proteins than their conventional T cell counterparts. Given that FOXP3, CTLA-4, and PD-1 are critical for Treg stability and/or function [5658], their diminished expression or transcriptional repression may compromise tumor-Treg survival and suppressive function as we observed in lung tumor-bearing, JQ1-treated mice. Although existing reports demonstrate that certain HDAC inhibitors affect Treg biology [35, 59, 60], and ricolinostat clearly evoked deleterious effects on patient tumor-Tregs in vitro , the more profound anti-Treg effect in our in vivo lung tumor model is attributed to JQ1.…”
Section: Discussionmentioning
confidence: 87%
“…These findings suggest that Treg cells may be more susceptible to epigenetic modifications by bromodomain proteins than their conventional T cell counterparts. Given that FOXP3, CTLA-4, and PD-1 are critical for Treg stability and/or function [5658], their diminished expression or transcriptional repression may compromise tumor-Treg survival and suppressive function as we observed in lung tumor-bearing, JQ1-treated mice. Although existing reports demonstrate that certain HDAC inhibitors affect Treg biology [35, 59, 60], and ricolinostat clearly evoked deleterious effects on patient tumor-Tregs in vitro , the more profound anti-Treg effect in our in vivo lung tumor model is attributed to JQ1.…”
Section: Discussionmentioning
confidence: 87%
“…Tregs play critical roles in tumor progression through suppressing cytotoxic CD8 + T‐cell proliferation, thereby favoring cancer cell escape from immunosurveillance. The expression of co‐inhibitory molecules including CTLA‐4, PD‐1, LAG‐3, TIM‐3, and TIGIT on Tregs is critically important for their suppressive function. Major mechanisms of immunosuppression include production of suppressive cytokines, direct cytolysis, metabolic arrest, and dendritic cell (DC) suppression through cell‐to‐cell contact‐dependent and independent mechanisms .…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the absence of PD1 on Treg cells led to generation of ex-Foxp3 T cells (42). However, Foxp3 stability was maintained in the absence of LAG3 on Treg cells, suggesting distinct pathways are regulated by LAG3 in Treg cells.…”
Section: Discussionmentioning
confidence: 99%